1999
DOI: 10.1016/s0893-133x(99)00050-0
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol Improves Membrane Phospholipid Abnormalities in Temporal Lobes of Schizophrenic Patients

Abstract: Functional neuroimaging studies have revealed abnormalities in the brains of schizophrenic patients, especially in the frontal and temporal lobes, basal ganglia, and thalamus (Bertolino et al. 1996;Andreasen et al. 1997;Egan and Weinberger 1997;McClure et al. 1998). Frontal lobe dysfunction generally has been associated with "negative" symptoms and the disorganization syndrome (Liddle et al. 1992;Kaplan et al. 1993;Shioiri et al. 1994;Deicken et al. 1995), whereas temporal lobe dysfunction may be related to "p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 35 publications
0
14
0
2
Order By: Relevance
“…In prefrontal brain regions, deficits of membrane lipid precursors were found more pronounced in follow-up investigations after antipsychotic treatment (Keshavan et al, 1989). Increased breakdown products of membrane lipids normalized after antipsychotic treatment in prefrontal (Stanley et al, 1995) and temporal (Fukuzako et al, 1999) brain regions. Therefore, the effects in several regions are likely to reflect the different etiology as well as timing of changes in these brain regions.…”
Section: Discussionmentioning
confidence: 90%
“…In prefrontal brain regions, deficits of membrane lipid precursors were found more pronounced in follow-up investigations after antipsychotic treatment (Keshavan et al, 1989). Increased breakdown products of membrane lipids normalized after antipsychotic treatment in prefrontal (Stanley et al, 1995) and temporal (Fukuzako et al, 1999) brain regions. Therefore, the effects in several regions are likely to reflect the different etiology as well as timing of changes in these brain regions.…”
Section: Discussionmentioning
confidence: 90%
“…At least crosssectional comparison of PLA2 activity (Smesny et al, 2005), niacin sensitivity and in vivo 31P-MRS (Smesny et al, 2005;Stanley et al, 1995) between first episode and chronic schizophrenia patients and matched controls support the notion of a stage dependency of membrane lipid changes. While the membrane breakdown could be influenced by antipsychotic treatment (Fukuzako et al, 1999b), the first-episode studies in neuroleptic-naïve patients indicate that medication effects do not explain the observed membrane changes at the on-set of illness.…”
Section: Discussionmentioning
confidence: 96%
“…However, PDEs were only increased in drug naïve and newly diagnosed medicated patients, implying a higher membrane phospholipid turnover at the onset of illness. Another explanation for this finding may be that antipsychotics inhibit the breakdown of membrane phospholipids (Fukuzako et al, 1999b). Using proton-decoupling in chronic medicated patients with schizophrenia, Potwarka et al (1999) unexpectedly found that the glycerol-3-phosphoethanolamine (GPEth) peak, and glycerol-3-phosphocholine (GPCh) peak were both normal, but the broader underlying phospholipid peak (probably lysosomal or peroxisomal) was higher, potentially suggesting excessive pruning (Keshavan et al, 1994) or excessive apoptotic activity (Ferri & Kroemer, 2001).…”
Section: Membrane Chemistry Assessed By 31 Phosphorus Mr Spectroscopymentioning
confidence: 99%
“…Diese Ergebnisse wurden in einer späteren Studie bestätigt und korrelierten mit Positivsymptomen gemessen mit der Brief Psychiatric Rating Scale (BPRS) [15]. In einer weiteren Studie reduzierte die Behandlung mit Haloperidol bei vorher unmedizierten Patienten die initiale Erhöhung der PDE im temporalen Kortex, allerdings nur teilweise, so dass die medizierten Patienten am Ende immer noch höhere Werte als die Kontrollpersonen aufwiesen [16].…”
Section: Introductionunclassified